Characterization of S-layer proteins of Lactobacillus by FTIR spectroscopy and differential scanning calorimetry - Mobili, Pablo (2009)
FTIR spectroscopy was used for the characterization of S-layer proteins extracted from microorganisms isolated from kefir grains. S-layer from Lactobacillus brevis ATCC 8287 has been already characterized [G. Vidgren, I. Palva, R. Pakkanen, K. Lounatmaa, A. Palva, J. Bacteriol. 174 (1992) 7419] and therefore it was used for the validation of FTIR as a method to investigate the secondary structure of the S-layer proteins of the studied kefir strains. A correlation between the secondary structures of S-layer proteins with surface properties of Lactobacillus kefir strains was found: a high percentage of b-sheet contents (40?50%) was found for non-aggregating strains, whereas this percentage decreased to 25?30% for aggregating ones. A quantitative comparison of the S-layers was performed by means of cluster analysis based on the obtained spectroscopic data. This analysis enabled the strains to be grouped in clusters according to the spectral diversity in the Amide I region. The non-aggregating strains of L. kefir cluster at Ssm > 0.943 and the aggregating strains form another cluster, with Ssm > 0.769. L. brevis ATCC 8287 appears clearly separated from these two clusters: the similarity with the aggregating strains is 0.658 and the similarity with the non-aggregating ones, 0.665. The thermal analysis of the lyophilized S-layer proteins was performed by means of differential scanning calorimetry (DSC) and FTIR. DSC analysis within the 30? 130 8C range showed two phase transitions with maxima located at ca. 58 and 98 8C for L. brevis and in the 67?70 and 110?119 8C ranges for the different strains of L. kefir (CIDCA 8344 only shows the lowest temperature phase transition). FTIR spectra obtained reveal that for all the L. kefir S-layer proteins the major secondary structure modifications upon heating occur nearly at the first phase transitions observed by DSC, with the thermal stability increasing with the percentage of b-sheets structures. The Slayer protein of L. brevis ATICC 8287, which among all protein studied is that with maximum b-sheet contents (and no a-helix structure) was then found to be the protein showing a greater thermal stability.